Os "claros" e "escuros" do discurso ideológico : a ideologia subjacente aos textos de enfermagem em centro-cirúrgico - Bottosso, Rosa Maria (1997)
This study has as general objective to analyze ideology discourse subjacent to the nursing texts in Operating Roon. what were used for Nursing Scool s teachers in Brazil, from 1990 until 1996 Specifically, it itself proposed to identify the bibliographic material used in nursing theaching in Operation Roon Nursing at Brazilian Scool; verify and to analyse the ideolgy discourse spreaded on nursing text in Operating Roon Nursing. It was used like methodological presupposed the historical materialism, once it’s articulated with the discourse analysis, turning the contextualizated interpretation easier historical and socielly. It is divided in four chapters. In the first —The ideology and its implications in education it was developed a concep of ideology. curriculum and the written language. In the second — The present ideology in the surgical practices along the history — it was rescued the important aspects of the surgical practices that interfered in the way of being and thing of the Operating Room s Nurse. In the third Ideology Implication in education of nurses that act in Operating Room it was tned to identify the way this content was being introduced at schools through minimum curriculun and it was made a general landscape of nursing Schools that are present in the sample. In the fourth Nursing texts in Operating Room and their occult sense it was builded up from an analysis of ideology discourse of the selected texts Starting from them, we ve got five basic categories: the operation room nurse’s knowledge and her articulation with instituted power in health area; the nurse’s position in the surgical group; the space as power expression; the roles attributed to the nurses; the ideology difusion through the spreaded images on the text In the first, we conclude nurse knowledge proceed along a biomedical model in running away of the ideology that value the techical knowledge for maintain Service of hegemonic classes’ interest of capitalist society In the second category, it was evidenced the nurse tradicional position while administrator/inspector boss who supplies the production needs and stands like surgeon s assistant In the third category The space as power expression the texts showed the absence of a specifc place to the nurse. while leader and participant of a group. In the fourth category — The roles attributed to the nurses it became evident the attribuitions made to the nurse as a prefessional proceed along the traditional models of adrninistration. and frorn non articulated participation criticai end political. Abouth the ideology diffusion through the spreaded images on the used text to the nurse teaching in operating room, it was inquired, through representative symbols in society, images that keep the professional in a making considered smaller end dismembered while Science. Finisches, recommending the books and articles used in teaching, must be investigated, once the ones shelter the ruling ideology, transmitting it through the dicourse apparently scientific In this perspective, the nurse must, when developing the knowledge, get in several forms language offers, instruments that subsidize the development of the criticai thinking with the purpose of, besides comprehending the world around it, to act on it.